2018
DOI: 10.1177/0003702818772856
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Coal Analyzer Using Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: Determination of coal quality plays a major role in coal-fired power plants and coal producers for optimizing the utilization efficiency and controlling the quality. In this work, a rapid coal analyzer based on laser-induced breakdown spectroscopy (LIBS) was developed for rapid quality analysis of pulverized coal. The structure of the LIBS apparatus was introduced in detail. To avoid time-consuming and complicated sample preparation, a pulverized feeding machine was designed to form a continuously stable coal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For example, Wang 6 et al investigated the intensity and stability of C and H lines in LIBS spectra that are highly related to the calorific value of coal in the atmosphere, helium and argon respectively, and conducted the quantitative analysis using partial least squares (PLS), and found that the signal to noise ratio as well as the prediction accuracy were the best in argon. Yao 7 et al used artificial neural networks and genetic algorithm to analyze the LIBS spectra of pulverized coal, and the average absolute error and standard deviation of calorific value were 0.48 MJ kg −1 and 0.86 MJ kg −1 , respectively. Although LIBS has great potential in online analysis and remote detection, its measurement repeatability is difficult to be further improved due to the laser pulse energy fluctuation, Rayleigh–Taylor instability, self-absorption effects, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang 6 et al investigated the intensity and stability of C and H lines in LIBS spectra that are highly related to the calorific value of coal in the atmosphere, helium and argon respectively, and conducted the quantitative analysis using partial least squares (PLS), and found that the signal to noise ratio as well as the prediction accuracy were the best in argon. Yao 7 et al used artificial neural networks and genetic algorithm to analyze the LIBS spectra of pulverized coal, and the average absolute error and standard deviation of calorific value were 0.48 MJ kg −1 and 0.86 MJ kg −1 , respectively. Although LIBS has great potential in online analysis and remote detection, its measurement repeatability is difficult to be further improved due to the laser pulse energy fluctuation, Rayleigh–Taylor instability, self-absorption effects, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are many reports on coal quality analysis by LIBS. Yao et al 6 combined cluster analysis, artificial neural networks (ANNs), and genetic algorithms (GA) to analyze the LIBS spectra of pulverized coal, and the mean standard deviation (SD) of the calorific value was 0.86 MJ kg −1 . Lu et al 7 also used the spectral analysis method of ANNs combined with GA to conduct LIBS analysis on the calorific value of coal, with an SD of 0.38 MJ kg −1 .…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the efficacy of a coal processing method and determine whether or not it is improving efficiency, the detection of coal composition is essential [1,2]. Methods such as X-ray fluorescence (XRF) and prompt gamma neutron activation analysis (PGNAA) have recently been used for coal analysis and measurements [3][4][5][6]. However, these methods can exert radiation hazards and are very expensive, so an alternative analysis method that is simultaneously safe and cost-effective is highly desired.…”
Section: Introductionmentioning
confidence: 99%